Semiconducting, biodegradable and bioactive fibers for drug delivery - M. M. Perez-Madrigal; E. Llorens; L. J. del Valle; J. Puiggali; E. Armelin; C. Aleman (eXPRESS Polymer Letters, 2016)
In this work we present the drug release properties and morphological studies of fibers formed by mixing different ratios of poly(lactic acid) (PLA) and poly(3-thiophene methyl acetate) (P3TMA) loaded with four drugs (ciprofloxacin, chlorhexidine dihydrochloride, triclosan and ibuprofen sodium salt). Thus, the main aim of this study is to prove that the excellent cellular response of PLA-P3TMA biocompatible scaffolds can be successfully combined with essential applications as drug carrier and delivery systems. Atomic force microscopic (AFM) and scanning electron microscopic (SEM) micrographs of PLA-P3TMA fibers indicate that the presence of the conducting polymer inside the PLA matrix affects the surface morphology, resulting in a significant increment of the bulk conductivity with respect to PLA fibers. Electrospun hybrid fibers of PLA and P3TMA successfully load both hydrophilic and hydrophobic drugs, the release profiles depending on the release environment (i.e. the release rate increases with the hydrophobicity of the medium). Finally, our results prove that the antibacterial activity of the drugs is not affected by their interactions with the PLA-P3TMA matrix.